The endonasal endoscopic management of pediatric lateral frontal mucocele - AlShakhs, Abdullah (Int J Surg Case Rep, 2021)
OBJECTIVES: The aim of this report is to show the usefulness of endoscopic sinus surgery in management of lateral frontal mucocele in pediatric patient. CASE PRESENTATION: A 14 years old girl presented with right frontal bone depression and headache. CT and MRI showed lateral mucocele occupying the right frontal sinus. The patient was managed successfully by image-guided endoscopic sinus surgery and she was well after two years follow up. DISCUSSION & CONCLUSION: Frontal mucoceles in children are rare. We report a rare case of a child with lateral frontal mucocele with no known etiology, treated successfully by image-guided endoscopic sinus surgery with no recurrence after two years follow-up. This case shows the usefulness of image-guided endoscopic sinus surgery in treatment of lateral frontal mucocele in children.